Modelling multi-species response to landscape dynamics: mosaic cycles support urban biodiversity - Kattwinkel, Mira; Strauss, Barbara; Biedermann, Robert; Kleyer, Michael (Landscape ecology, 2009)
The importance of the spatial as well as the temporal structure of habitat patches for urban biodiversity has been recognised, but rarely quantified. In dynamic environments the rate of habitat destruction and recreation (i.e. the landscape turnover rate), the minimum amount of potential habitat, its spatial configuration as well as the environmental conditions determining habitat quality are crucial factors for species occurrence. We analysed species responses to environmental parameters and to the spatio-temporal configuration of urban brownfield habitats in a multi-species approach (37 plant and 43 insect species). Species presence/absence data and soil parameters, site age, vegetation structure and landscape context were recorded by random stratified sampling at 133 study plots in industrial areas in the city of Bremen (Germany). Based on the field data, we predicted species occurrences by species distribution models using a multi-model inference approach. Predicted species communities were driven by successional age both at the scale of a single building lot and at the landscape scale. Minimum average succession time of brownfield habitats required to support all and especially regionally rare species depended on the proportion of available open space; the larger the potential habitat area the faster the acceptable turnover. Most plant, grasshopper, and leafhopper species modelled could be maintained at an intermediate turnover rate (mean age of 10–15 years) and a proportion of open sites of at least 40%. Our modelling approach provides the opportunity of inferring optimal spatio-temporal landscape configurations for urban conservation management from patch scale species-environment relationships. The results indicate that urban planning should incorporate land use dynamics into the management of urban biodiversity.